Isolation and characterization of the outer membrane of Escherichia coli with autodisplayed Z-domains - Park, Min; Yoo, Gu; Bong, Ji-Hong; Jose, Joachim; Kang, Min-Jung; Pyun, Jae-Chul (ELSEVIER SCIENCE BV, 2015)
"Autodisplay technology" is an expression technique used to display the various recombinant proteins on the outer membrane (OM) of Escherichia coli. The resulting autodisplayed Z-domain has been used to improve the sensitivity of immunoassays. In this work, a facile isolation method of the OM fraction of E. coli with autodisplayed Z-domains was presented using (1) an enzyme reaction for the hydrolysis of the peptidoglycan layer and (2) short centrifugation steps. The purity of the isolated OM fraction was analyzed. For the estimation of contamination with bacterial proteins from other parts of E. coli, Western blots of marker proteins for the OM (OmpA), periplasm (beta-lactamase), inner membrane (SecA), and cytoplasm (beta-galactosidase) were performed. Additionally, assays of marker components or enzymes from each part of E. coli were carried out including the OM (KDO), inner membrane (NADH oxidase), periplasm (beta-lactamase), and cytoplasm (beta-galactosidase). The yield of OM isolation using this new method was determined to be 80% of the total OM amount, with less than 1% being contaminants from other parts of E. coli. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: E. COLI; PROTEIN-A; SPR BIOSENSOR; IMMUNOASSAY; ASSAY; BETA; SURFACE; CELLS; LAYER